Control of Wind-Power Systems Operating at Variable Wind Speeds to Optimize Energy Capture - Cristian Paul Chioncel; Samuel Ciucurita; Elisabeta Spunei (Energies)
This paper examines two contradictory aspects of wind turbine operation: the positive aspect of functioning at the maximum power point (MPP) and the negative aspect of power gaps that occur during significant fluctuations in wind speed. The analysis utilizes experimental data from a 2.5 MW wind turbine operating in the Dobrogea region, focusing on identifying the optimal energy zone. To maintain operation within this optimal zone, a control algorithm based on kinetic energies is developed. The control aims to adjust the load on the electric generator in relation to the wind speed value. The proposed approach ensures operation within the MPP through a control algorithm based on kinetic energies, which adjusts the load on the generator according to the wind speed values.